2001
DOI: 10.1046/j.1540-8167.2001.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Reentrant Circuit of Verapamil‐Sensitive Idiopathic Left Ventricular Tachycardia: Direct Evidence for Macroreentry as the Underlying Mechanism

Abstract: The exact reentrant circuit of verapamil-sensitive idiopathic left ventricular tachycardia (ILVT) remains unclear. This case report demonstrates the reentrant circuit of ILVT. A 20-pole electrode catheter was placed along the left posterior fascicle during electrophysiologic study. ILVT was reproducibly induced by programmed ventricular stimulation. During the tachycardia, sequential diastolic potentials bridging the entire diastolic period were observed in the recordings from the electrodes positioned from le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 18 publications
0
61
0
Order By: Relevance
“…7 In this arrhythmia, discrete fascicular potentials can be recorded over a significant portion of the interventricular septum at the site of successful ablation. [7][8][9] In addition, this arrhythmia demonstrates the classic criteria for transient entrainment with rapid ventricular pacing and has been conclusively demonstrated to be due to a macro-reentrant circuit. 9,14 Interfascicular reentry and automatic fascicular VTs usually occur in patients with dilated cardiomyopathy, although they may also occur in structurally normal hearts.…”
Section: Differential Diagnosismentioning
confidence: 85%
See 1 more Smart Citation
“…7 In this arrhythmia, discrete fascicular potentials can be recorded over a significant portion of the interventricular septum at the site of successful ablation. [7][8][9] In addition, this arrhythmia demonstrates the classic criteria for transient entrainment with rapid ventricular pacing and has been conclusively demonstrated to be due to a macro-reentrant circuit. 9,14 Interfascicular reentry and automatic fascicular VTs usually occur in patients with dilated cardiomyopathy, although they may also occur in structurally normal hearts.…”
Section: Differential Diagnosismentioning
confidence: 85%
“…1,2 Fascicular VTs usually involve the posterior fascicle of the left bundle branch but may also involve the anterior fascicle or the upper septum of the LV 7 ; these forms of VT are often based on a reentrant mechanism and may be sensitive to verapamil. [7][8][9] We describe a distinct clinical syndrome of VT that is exercise induced and arises from the base of the posterior papillary muscle (PPM) in the LV.…”
mentioning
confidence: 99%
“…[4][5][6] The connection strand serves as the antegrade limb, the fascicles serves as the retrograde limb, and the earliest retrograde PP is usually recorded at the beginning of retrograde limb. 6 Partially conforming to those findings, the current study found that the earliest retrograde PP was recorded along the predefined LPF and averaged 15 mm away from its distal end. All VTs could be successfully abolished by ablation at the earliest retrograde PP.…”
Section: Depolarization Of Fascicle System and Ventricle During Ilvtmentioning
confidence: 99%
“…[2][3][4] Reentry involving the left His-Purkenje system (HPS) was thought to be the underlying mechanism. 5,6 Ablation directed at the earliest retrograde presystolic potential (PP) or diastolic potential (DP) was proved feasible and effective. 4,7 Functionally, the main branch of left HPS is insulated from the adjacent myocardium and exhibits isolated conduction during sinus rhythm (SR), but in vivo study in human beings is very limited.…”
mentioning
confidence: 99%
“…[18][19][20] A fibromuscular false tendon is a fine muscular strand which carries Purkinje fibers and may traverse the LV cavity between the PMs and the intraventricular septum. It is possible that in some cases of PM-FVT, there is an anatomical and electrical connection between the APM and PPM, which may explain the changes in QRS morphology from superior to inferior axis deviation during ablation.…”
Section: Relevance Of Fibromuscular False Tendon To Pm-fvtmentioning
confidence: 99%